Fertility Preservation in 2016: Where Are We? - David, Anu; Green, Lisa Jeannette; Shikanov, Ariella (Seminars in Reproductive Medicine, 2017)
This review focuses on advances in the field of fertility preservation achieved over the past few decades. The main purpose of fertility preservation is to help young cancer survivors retain their fertility by restoring either their ability to procreate or simply their reproductive endocrine function. Although different options are available in this regard, successful fertility preservation is yet to reach its full potential. Herein, we review the most significant work conducted over the past five decades and present new methodologies.
Keywords: fertility preservation; oocyte and embryo cryopreservation; ovarian tissue cryopreservation; whole ovary cryopreservation; artificial ovary; immunoisolation